2007
DOI: 10.1017/s1368980007702914
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of glycaemic index with cardiovascular risk factors: analysis of the National Diet and Nutrition Survey for people aged 65 and older

Abstract: Objective: To identify associations between dietary glycaemic index (GI) and weight, body mass index and other risk factors for cardiovascular disease (CVD) -waist-tohip ratio (WHR), lipoprotein fractions, triacylglycerols (TAG) and blood pressure (BP) -in an older British population. Design: Cross-sectional dietary, anthropometric and biochemical data from the National Diet and Nutritional Survey for adults aged over 65 years were reanalysed using a hierarchical regression model. Associations between body wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 53 publications
(88 reference statements)
0
22
0
Order By: Relevance
“…Very few observational studies have investigated the association between GL (or GI) and BP. In the British National Diet and Nutritional Survey, GI was not associated with SBP or DBP in participants over 65 years of age [33]. Intervention studies have produced equivocal results, with some showing no effect of reduced-GL/GI diets on BP [34] and others showing trends toward reductions in both SBP and DBP on such diets [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Very few observational studies have investigated the association between GL (or GI) and BP. In the British National Diet and Nutritional Survey, GI was not associated with SBP or DBP in participants over 65 years of age [33]. Intervention studies have produced equivocal results, with some showing no effect of reduced-GL/GI diets on BP [34] and others showing trends toward reductions in both SBP and DBP on such diets [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…The associations between GI and GL and different blood lipids are fairly consistent in the cross‐sectional studies, with protective effects of both GI and GL on TAG and HDL‐C 50,52,55–57,59 and no association with TC and LDL‐C 16,32,49,50,52,53 . On the other hand, the two prospective studies that examined associations between GI and GL and these blood lipids 53,54 were unable to replicate the findings from cross‐sectional studies; hence, GI and GL do not seem to influence changes in blood lipids.…”
Section: Blood Lipidsmentioning
confidence: 55%
“…Inverse cross‐sectional associations between GI and high‐density‐lipoprotein cholesterol (HDL‐C) were observed in six studies, 38,50–53,55 whereas four other cross‐sectional studies did not find significant associations 16,32,49,56 . Neither of the two longitudinal studies identified significant associations between GI and change in HDL‐C 53,54 (Table 5).…”
Section: Blood Lipidsmentioning
confidence: 97%
See 2 more Smart Citations